The Trade Relations between Turkey and United Kingdom after Brexit and in the Covid-19 Epidemic - Uzunoglu, Sadi; Atakişi, Ahmet; Aktaç, Orkun (Bulgarian Journal of International Economics and Politics, 2021)
In the process of globalization, where international economic relations have further increased their significance, the separation of United Kingdom from the EU (Brexit) has literally called into question the understanding of integration. It is also noteworthy that the Brexit event coincided with the trade wars between the USA and China and the beginning of the new regional unions that China has established in the Pacific. Undoubtedly, these developments will significantly affect the future of world trade. Slowing economic growth in the world economy, deterioration in income and wealth distribution, increasing indebtedness rates, falling productivity and the threat of the COVID-19 epidemic in terms of world trade volume are commonly discussed. Especially during the COVID-19 epidemic, the supply constraints, the breaks in supply chains and the problems in logistics sector, are generally seen to mark the beginning of important changes in international trade. And Brexit has taken place amid such severe conditions. Naturally, it will have consequences for almost every country. Brexit is likely to have an effect not only on the fully-fledged members of the EU, but also on countries outside the EU. The EU and the UK are important partners in Turkey’s foreign trade. Hence the question of How Brexit will affect the trade between UK and Turkey, given Turkey’s customs union agreement with the EU has lately topped Turkey’s agenda. This study aims to discuss Turkey’s foreign trade with England prior to Brexit as well as the possible developments after Brexit.